Melacak Keserasian Nilai Pendidikan Islam dan Dolabololo - Ibrahim Muhammad (IAIN Ternate, 2022)
Islamic education is an effort to develop human potential, both physically and spiritually, which aims to form a whole human being who is happy, and safe in this world and the hereafter. Dola Bololo as part of Ternate's oral literature, which has been passed down from generation to generation, has a polite and gentle meaning and style of language, teaching humans about the essence of life. This research includes library research, using descriptive qualitative methods with a hermeneutic approach, namely the study of hidden meanings in texts, used to internalize and understand in depth the phenomenon of oral literary culture in the people of the Ternate sultanate. The data sources used are primary data sources and secondary data sources. The data collection method is a method as a data collection tool, so the analysis strategy used is content analysis. After that, the researcher tries to present it in an analytical descriptive manner, namely an effort to collect data, compile the necessary data, then analyze and interpret the data. One of the ways to encourage the religious people of Ternate to understand and practice Islamic teachings, which include the Shari'a creed and worship, is Dola Bololo being an effective means of conveying the messages of heaven to the inhabitants of the earth. The researcher's interest is trying to find harmony between the values of Islamic education and Dola Bololo, as a contribution to caring for and preserving Dola Bololo, as well as encouraging the Ternate generation, for the intelligence of their ancestors, choosing a method of teaching Islam to the public using language that is easy to understand, through compositions of Dola Bololo.